Increased Plasma Heparanase Activity in COVID-19 Patients - Buijsers, Baranca; Yanginlar, Cansu; de Nooijer, Aline; Grondman, Inge; Maciej-Hulme, Marissa L.; Jonkman, Inge; Janssen, Nico A. F.; Rother, Nils; de Graaf, Mark; Pickkers, Peter; Kox, Matthijs; Joosten, Leo A. B.; et al. (Frontiers in Immunology, 2020)
Reports suggest a role of endothelial dysfunction and loss of endothelial barrier function in COVID-19. It is well established that the endothelial glycocalyx-degrading enzyme heparanase contributes to vascular leakage and inflammation. Low molecular weight heparins (LMWH) serve as an inhibitor of heparanase. We hypothesize that heparanase contributes to the pathogenesis of COVID-19, and that heparanase may be inhibited by LMWH. To test this hypothesis, heparanase activity and heparan sulfate levels were measured in plasma of healthy controls (n=10) and COVID-19 patients (n=48). Plasma heparanase activity and heparan sulfate levels were significantly elevated in COVID-19 patients. Heparanase activity was associated with disease severity including the need for intensive care, lactate dehydrogenase levels and creatinine levels. Use of prophylactic LMWH in non-ICU patients was associated with a reduced heparanase activity. Since there is no other clinically applied heparanase inhibitor currently available, therapeutic treatment of COVID-19 patients with low molecular weight heparins should be explored.